Avaliação da opalescência, refletância, transmitância e atenuação de resinas compostas em função do tempo - Pepelascov, Daniele Esteves (2014)
To evalute the Opalescence Parameter (OP), reflectance spectra (R(λ )), transmittance spectra (T(λ)) and attenuation coefficient (٥(λ )) of composite resins, immeaditly after preparation and after 2, 7, 30, 60, 120 and 180 days of storage and compare with the results obtained for human enamel. For this purpose, 20 samples of enamel (5.0 mm x 0.3 mm) and 9 samples (10.0 mm x 1.0 mm) were made up of 10 different shades of commercial composite resins available on the national market: Empress Direct (Ivoclar Vivadent), Enamel Plus HRI (Miscerium), Filtek Z350 XT (3M Espe), Llis (FGM) and Opallis (FGM). As a control group, 9 samples of adhesive Ambar (FGM) were fabricated. The reading of the spectra R(λ) and T(λ) was performed by spectrophotometry, using the integrating sphere. The ٥(λ) was calculated in terms of (R(λ)) and (T(λ)) and OP was calculated as the difference between the yellow-blue coordinates (Δb*) and red-green coordinates (Δa*) between the reflected and transmitted light, using color scale CIE L*a*b* (1976). The data were statistically analyzed (ANOVA and Tukey). Results: Only one of the resins had statistically similar values of OP to the enamel during the study period. The resins showed high value of OP, which for some brands remained stable and others increased over time. For resins that had increased their OP, there was a shift to yellow for both T(λ) and for R(λ). The OP does not have clinical applicability, in other words, resins with high values of opalescence not necessarily reproduce a greater reflection of cool colors and greater transmission of warm colors.